Warehouse Pests of Agricultural Products - Egamberdi o‘g‘li, Murodov Baqojon; Qodir o‘g‘li, Qodirov Nodir (American Journal of Biology and Natural Sciences, 2026)
Pests of stored products are key limitations for the safekeeping and quality maintenance of food commodities globally [5]. In this work the species composition, spreading, harmfulness and biocontrol potential of most important storages pests of grain, leguminous and dried fruit products are considered. Research has centered on insect pests in the order Coleoptera, which are preeminent and most destructive storage ecosystem organisms. Economic pests such as Tribolium confusum, Tenebrio molitor, Sitophilus granarius, Sitophilus oryzae, Oryzaephilus surinamensis, Callosobruchus maculatus and Plodia interpunctella were found by field observations under the laboratory conditions. These insects damage our crops due to their feeding, contamination and product quality loss with economic losses across storage, processing and transportation situations.